Incomplete Kawasaki disease: Experience with 14 patients with cardiac complications - Abuhammour, Walid; Yousef, Nida (Journal of Pediatric Infectious Diseases, 2008)
Due to lack of a specific diagnostic test, the diagnosis of Kawasaki disease (KD) can only be made based on fever associated with characteristic clinical features and exclusion of other diseases with similar presentation. Incomplete presentation has been repeatedly described and often leads to delay in diagnosis, which may result in coronary artery involvement. During an eight-year study period (1991–1998), 14 patients with incomplete KD with cardiac complications were identified. Age range was 3.5 months to 13 years; 11 patients were ≤ 5 years of age. Fever lasting ≥ 5 days was present in all 14 patients, 10 of whom had a temperature ≥ 40°C. Three diagnostic clinical criteria of KD were present in seven patients, two criteria in five patients, and one criterion in two patients. Echocardiography showed ectasia/aneurysm of at least one coronary artery in all patients. Coronary artery involvement was detected and treated after 5–7 days of illness in 50% of the patients, after 7–10 days in 29%, and after 10 days in 21% of the patients. All patients had elevated erythrocyte sedimentation rate (ESR) (mean ESR =48 mm/h). Twelve patients had leukocyte count ≥ 16,000/mm3. All patients were treated with Intravenous Immunoglobulin (IVIG) and oral aspirin. Clinical and echocardiographic resolution occurred in 13 patients. One patient, whose diagnosis was made 25 days after the onset of fever, died of pulmonary hemorrhage secondary to a pulmonary artery aneurysm. Although this retrospective study is limited by the small number of patients, it showed that children with incomplete KD-especially ≤ 5 years of age-with high fever (≥40°C), leukocytosis (≥ 16.000/mm3) and elevated ESR (≥ 40 mm/h), developed cardiac complications as early as the fifth day of illness. We suggest that earlier diagnosis and prompt treatment with intravenous gamma globulin before the fifth day of fever might reduce cardiac complications.
Keywords: Incomplete Kawasaki disease; cardiac complications